Effects of TolC on the pathogenicity of porcine extraintestinal pathogenic Escherichia coli - Hu, Jin; Wang, Dongfang; Huang, Xingfa; Yang, Yang; Lian, Xin; Wang, Wenjun; Xu, Xiao; Liu, Yulan (Frontiers in Immunology, 2022)
Extraintestinal pathogenic Escherichia coil (ExPEC) is a well-known critical pathogenic zoonosis that causes extra-intestinal infection in humans and animals by affecting their immune organs. At present, research on the outer membrane protein tolerant colicin (TolC) of E. coli, a virulent protein in the formation of ExPEC efflux pump, has been an attractive subject. However, its pathogenic mechanism is still unclear. To further explore the role of TolC in the pathogenesis of ExPEC strain PPECC42, a complementation strain (Cm-TolC) as well as an isogenic mutant (ΔTolC) were constructed. Loss of TolC drastically impaired the virulence of ExPEC in the experimental mice model. ΔTolC showed a substantial decrease in PAVECs adherence, invasion and pro-inflammatory response in contrast to that of the wild type (WT), with a reduced survival ratio in both the bacterial load and whole blood in mice. ΔTolC also had decreased protein expression of necroptosis signlas suchs as receptor-interacting protein kinase (RIP) 1, phosphorylated mixed-lineage kinase domain-like protein (MLKL), and mitochondrial proteins such as phosphoglycerate mutase family member 5 (PGAM5). Our available data suggest that TolC is closely associated with the pathogenesis of ExPEC. Here, our study will provide scientific grounds for exploring the potentiality of TolC as an effective drug target for controlling the infection of ExPEC, screening new inhibitors, as well as developing new drugs. All that for the purpose of further preventing and controlling the infection of ExPEC.